Optimización del transporte de materiales desde el área de abastecimiento a la línea de ensamble en la empresa Ciauto. - Erazo Mejía, Juan Carlos (2023)
The CIAUTO CIA. LTDA., company is responsible for the assembly and import of Chinese vehicles of different ranges. Among them are brands such as: Haval, Soueast, Wingle, SHINERAY, GLORY, among others. These brands have gained increased demand, so an adequate stick supply is needed to meet the required production peaks. Thus, problems have been identified,such as the lack of handling the traceability of components, delay in line loading times, the increase in labor costs and lack of productive efficiency for the company. This project focused on implementing an efficient system for transporting Completed Known Disassembled (CKD) components to assembly line stations using a disused electric car that in turn is provided by the supplier area. The development of the proposal took about 8 months, o time in which the Waterfall methodology has been used to determine the requirements of the system, design and validate it, also relying on descriptive and exploratory research. Once the respective validation has been carried out it has been determined that the transport system of line load by using the electric car, would save CIAUTO USD 54,98 in the production process and also having a decrease of 540 minutes in working hours and will increase the production of an additional monthly unit in the brand SHINERAY and eight units in Great Wall. Finally, the execution of this project allowed to demonstrate a feasible option for the improvement of the productive process in CIAUTO CIA. LTDA.